Implementation of Religious Moderation in Kain Golong Village (Study on KEPDIRJEN BIMAS Islam Number 137 Of 2023) - Purwanto, Purwanto; Nurasiah, Nurasiah; Siregar, Ramadhan Syahmedi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research explores the implementation of religious moderation in Kain Golong Village, Simpang Kanan District, Aceh Singkil Regency. The study is grounded in the Decree of the Director General of Islamic Community Guidance Number 137 of 2023, which provides guidelines for establishing religious moderation villages. Using a qualitative approach that combines field studies and literature reviews, data was collected through observations, interviews, and documentation from various sources, including village officials, religious leaders, and community members. The findings reveal that the designation of Kain Golong as a village of religious moderation was conducted according to the prescribed procedures. The community's daily practices reflect a commitment to religious moderation, demonstrated through educational activities, mutual assistance in religious celebrations, and the inclusive participation of both Muslims and non-Muslims in social, religious, and governmental activities. This research highlights the successful application of religious moderation principles in fostering tolerance and safeguarding national unity.